Opposing Roles of Calcium and Intracellular Atp on Gating of the Purinergic P2x2 Receptor Channel - Leiva-Salcedo, D (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
P2X2 receptors (P2X2R) exhibit a slow desensitization during the initial ATP application and a progressive, calcium-dependent increase in rates of desensitization during repetitive stimulation. This pattern is observed in whole-cell recordings from cells expressing recombinant and native P2X2R. However, desensitization is not observed in perforated-patched cells and in two-electrode voltage clamped oocytes. Addition of ATP, but not ATPγS or GTP, in the pipette solution also abolishes progressive desensitization, whereas intracellular injection of apyrase facilitates receptor desensitization. Experiments with injection of alkaline phosphatase or addition of staurosporine and ATP in the intracellular solution suggest a role for a phosphorylation-dephosphorylation in receptor desensitization. Mutation of residues that are potential phosphorylation sites identified a critical role of the S363 residue in the intracellular ATP action. These findings indicate that intracellular calcium and ATP have opposing effects on P2X2R gating: calcium allosterically facilitates receptor desensitization and ATP covalently prevents the action of calcium. Single cell measurements further revealed that intracellular calcium stays elevated after washout in P2X2R-expressing cells and the blockade of mitochondrial sodium/calcium exchanger lowers calcium concentrations during washout periods to basal levels, suggesting a role of mitochondria in this process. Therefore, the metabolic state of the cell can influence P2X2R gating. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.